2001
DOI: 10.1021/jp012969v
|View full text |Cite
|
Sign up to set email alerts
|

Through-Space Charge and Dipolar Effects in Substituted Ethanes and 1,1,1-Trifluoroethanes

Abstract: The results of ab initio calculations with the 6-31+G* basis set are reported on over sixty compounds of the type CZ 3 CH 2 X (Z ) H, F) and on a few longer chain-substituted alkanes. Data for the eclipsed conformations with Z ) H and both the staggered and eclipsed conformations with Z ) F are presented. The charges on the atoms in these molecules are determined with the Atoms in Molecules (AIM) and Natural Population Analysis (NPA) methods of analysis. The charges on the fluorine atoms in the trifluoroethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…For instance, the Mulliken and NAO negative charges on the carbon atom of the CH 3 group are considerably larger in CH 3 CF 3 than in ethane . The computed charges on the central carbon atom of propane, CF 3 CH 2 CH 3 , and CF 3 CH 2 CF 3 are similar, which is in accord with the fact that CF 3 CH 2 CF 3 is not nearly as CH-acidic as CF 3 CH 2 CN . Apparently, the β-effect might well take place in trifluoromethyl complexes of metals, as can be seen from the remarkably similar charge distribution trends shown in Schemes and .…”
Section: Trifluoromethyl and Perfluoroalkyl Derivatives Of Catalytic ...supporting
confidence: 58%
“…For instance, the Mulliken and NAO negative charges on the carbon atom of the CH 3 group are considerably larger in CH 3 CF 3 than in ethane . The computed charges on the central carbon atom of propane, CF 3 CH 2 CH 3 , and CF 3 CH 2 CF 3 are similar, which is in accord with the fact that CF 3 CH 2 CF 3 is not nearly as CH-acidic as CF 3 CH 2 CN . Apparently, the β-effect might well take place in trifluoromethyl complexes of metals, as can be seen from the remarkably similar charge distribution trends shown in Schemes and .…”
Section: Trifluoromethyl and Perfluoroalkyl Derivatives Of Catalytic ...supporting
confidence: 58%
“…Studies have shown similar magnitudes of changes in position of bond CPs on small organic molecules due to the addition of electron withdrawing and donating groups. 34 , 35 Perturbations to wavefunctions that move CPs are due primarily to the orientations and positions of dipole moments from each atom in the surrounding protein, and will be most prominent for charged and polar residues, including the K + present in the 7 Å model for configurations 1 and 2.…”
Section: Discussionmentioning
confidence: 99%